Transfer Pusat dan Upaya Pendapatan Asli Daerah (Studi kasus Kabupaten/Kota di Kalimantan Barat) - Kartika, Metasari (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2015)
This study aims to obtain empirical evidence the impact of intergovernmental transfers on local revenue effort. This study uses unbalanced panel data from 14 Regency / Municipality in West Kalimantan Province during the period 2001 to 2009.The research concluded that (1) There are differences in the local revenue capacity in the Regency/Municipality West Kalimantan Province, causing the local revenue efforts was different, (2) On average in the Regency / Municipality West Kalimantan Province, DAU and DBH tax (unconditional transfers ) has a positive and significant effect on local revenue effort, (3) On average in the Regency / Municipality West Kalimantan Province, DAK (conditional transfers) has a negative and significant effect on local revenue effort.